Estrategias didácticas en el fortalecimiento de la ortografía en los estudiantes de octavo año de educación básica de la Unidad Educativa “Dr. Emilio Uzcátegui”. - Alcoser Villalobos, José Manuel (2024)
The present study aimed to design didactic strategies to enhance spelling skills among eighth grade students at Emilio Uzcátegui School in Guamote Canton, Chimborazo Province, during the 2023-2024 academic year. A mixed-methods approach was employed, integrating both quantitative and qualitative research techniques to gather comprehensive data. The research utilized observation, surveys, and interviews to systematically collect information on the variables affecting spelling proficiency, based on the input of a carefully selected student sample. Data analysis provided insights into the participants' opinions, behaviors, attitudes, and aspirations, offering a deeper understanding of the factors influencing their writing abilities. The study culminated in the development of a set of targeted didactic strategies, which were found to significantly improve students' spelling skills and, by extension, their overall writing competence in a globalized context.